2022
DOI: 10.3390/ijerph19148280
|View full text |Cite
|
Sign up to set email alerts
|

Does Digital Inclusive Finance Mitigate the Negative Effect of Climate Variation on Rural Residents’ Income Growth in China?

Abstract: Global anthropogenic greenhouse gas emissions have exacerbated climate variation. Climate variation impacts the agricultural production and rural residents’ income negatively, further widening the urban-rural income gap and harming the co-benefits. Narrowing the income gap has always been a global concern and an important part of China’s rural revitalization strategy. However, little is known about whether digital inclusive finance can mitigate the negative impact of climate variation on rural residents’ incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…As we mentioned in Section 3 , we divided households into two groups based on whether they had unhealthy household members and tested the effects of mobile payment in each group according to Yin et al (2019) [ 51 ] and He et al (2022) [ 58 ]. The results are reported in Table 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we mentioned in Section 3 , we divided households into two groups based on whether they had unhealthy household members and tested the effects of mobile payment in each group according to Yin et al (2019) [ 51 ] and He et al (2022) [ 58 ]. The results are reported in Table 8 .…”
Section: Resultsmentioning
confidence: 99%
“…To test whether health risks will lower the income level of rural residents, we applied the OLS model to Equation (3): where is our focus variable and the other variables are the same as Equation (1). Then, following Yin et al (2019) [ 51 ] and He et al (2022) [ 58 ], we divided samples in two groups depending on whether they had unhealthy household members. The effects of mobile payment on rural household income will be examined in each group to verify its moderating role.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusive nature of digital inclusive finance provides new ways to reduce financial poverty. Numerous studies have also confirmed that digital inclusive finance can increase the income sources and income scale of disadvantaged groups, narrow the income gap and achieve inclusive growth (Yu and Wang, 2021;He et al, 2022). The increase in income can promote consumption upgrading through the transmission mechanism of production restructuring and industrial upgrading Yang et al, 2021).…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 94%
“…DIF is a newly developing industry, formed based on the organic integration of digital technology and finance. It involves the application of the internet and big data technology and the effective integration of the concept of inclusive finance (He et al, 2022). DIF can play an essential role in promoting household consumption (Li et al, 2020).…”
Section: Digital Inclusive Financementioning
confidence: 99%
“…Studies in all these streams of literature tend to focus on the effects and mechanisms of DIF on the single economic behavior of households and the analysis of household economic behavior about each other. For example, previous studies have examined the relationship between DIF, and household financial investment and consumption behavior (He et al, 2022;Li et al, 2022;Yu et al, 2022). Particularly, how to measure the impact of DIF on household economic behavior when DIF affects both household financial investment and consumption has generally affected household behavioral choices and the inclusive application of DIF (Zhao et al, 2022).…”
Section: 3mentioning
confidence: 99%